2015
DOI: 10.1037/sgd0000130
|View full text |Cite
|
Sign up to set email alerts
|

“Without this, I would for sure already be dead”: A qualitative inquiry regarding suicide protective factors among trans adults.

Abstract: Despite an alarmingly high rate of attempted suicide among trans adults, few studies have investigated suicide protective factors among this population. The current study was aimed at identifying suicide protective factors among trans adults using a qualitative methodology. A sample of self-identified trans adults (N ϭ 133) was recruited from LGBT LISTSERVs across Canada. Participant were predominantly White and ranged in age from 18 to 75 years old (M ϭ 37). Qualitative data were collected online via open-end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 66 publications
0
74
0
Order By: Relevance
“…It is important to note that not all identified strength-based factors will achieve the same salubrious effects or operate for all individuals or groups in the same way. Some strength-based factors can act as negative predictors among certain groups and circumstances (e.g., social support; Mereish & Poteat, 2015;Moody, Fuks, Peláez & Smith, 2015). For example, higher levels of community consciousness have been shown to exacerbate the degree to which mental health mediates the relationship between discrimination and body image issues in sexual minority men (Simpson, Sutter, & Perrin, 2016).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…It is important to note that not all identified strength-based factors will achieve the same salubrious effects or operate for all individuals or groups in the same way. Some strength-based factors can act as negative predictors among certain groups and circumstances (e.g., social support; Mereish & Poteat, 2015;Moody, Fuks, Peláez & Smith, 2015). For example, higher levels of community consciousness have been shown to exacerbate the degree to which mental health mediates the relationship between discrimination and body image issues in sexual minority men (Simpson, Sutter, & Perrin, 2016).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Research over the last decade reveals an increasing trend toward distinguishing sex and gender with respect to health disparities. This work establishes a clear disadvantage among trans people regarding mental health outcomes, such as suicide (Clements‐Nolle, Marx, & Katz, ; Moody, Fuks, Peláez, & Smith, ), non‐lethal self‐harm (Reisner et al, ), and depression and anxiety (Budge, Adelson, & Howard, ). Explanations for these disparities include societal stigma (Hughto, Reisner, & Pachankis, ; Lombardi, ; Yang, Manning, van den Berg, & Operario, ), discrimination in healthcare settings (Bradford, Reisner, Honnold, & Xavier, ; Poteat, German, & Kerrigan, ; Reisner, Gamarel, Dunham, Hopwood, & Hwahng, ), low levels of familial support (Grossman & D'Augelli, ; Moody & Smith, ; Olson, Durwood, DeMeules, & McLaughlin, ), and histories of violence (Bradford et al, ; Kenagy, ; Stotzer, ).…”
Section: Gendered Health Inequalitymentioning
confidence: 82%
“…In addition, expectations of negative reactions toward their gender identity and internalized transphobia are associated with higher suicide ideation (Testa et al 2017). Individual factors that are potentially protective against suicide ideation include perceived coping abilities, optimism, gender identity acceptance and disclosure, and reasons for living (Moody and Smith 2013;Moody et al 2015;Testa et al 2017). Interestingly, Moody et al (2015) found that transgender people with intentions to or who actually transition reported less suicide ideation, which contrasts aforementioned findings by Rood et al (2015).…”
Section: Correlates Of Suicide Ideationmentioning
confidence: 88%